A 12 Minute, Single Tube, Nanogram Input Library Prep - Dunham, Joseph (J Biomol Tech, 2019)
Next Generation Sequencing (NGS) library construction is a workflow bottleneck. The processes of library construction for DNA and RNA sequencing are complex, error prone, costly, and in general are time consuming. Current commercial products offer multistep, multi-hour sample processing that can be cost and labor prohibitive. These issues have created a demand for a simple, rapid, and cost-effective library construction product that offers users application flexibility while minimizing construction complexity for low to ultra-high throughput sample processing. SeqOnce has developed a novel library technology that is rapid and minimizes sample processing complexity. The five tube kit is comprised of formatted master mixes for a simple and stable user workflow. The 12 minute library construction uses a single master-mix that when combined with fragmentation and PCR steps produces libraries in less than 50 minutes. A single size selection step occurs after PCR and the PCR free protocol is less than 20 minutes. The kit contains three master mixes and includes adapters, which maximally promotes product flexibility across multiple applications. With master-mixes that are stable for 7 days at ambient temperatures, automation on liquid handling platforms is effortless due to the simple workflow. The technology has been validated with samples ranging from microbial to human and supports a wide range of nucleic acid types and input range: 1ng - 200ng. The sequencing data is either equivalent or superior to other competing library products, with high mapping rates and excellent performance across variable GC content. The technology is currently optimized for the Illumina platform and alternative NGS platforms are under evaluation for future development.